Escaping Stigma and Neglect : People with Disabilities in Sierra Leone - Ovadiya, Mirey; Zampaglione, Giuseppe (World Bank, 2012)
The objective of this policy note on people with disabilities in Sierra Leone is to: (i) provide a diagnosis on the scale and nature of the problem; (ii) analyze current public policies in support of people with disabilities; (iii) review public and private programs; and (iv) propose some policy options to policy makers and development partners. This note contains five chapters, the first of which is this introduction. Chapter two summarizes the diagnosis of the scale and nature of the people with disabilities issue by examining the prevalence, types, and causes of disability and by discussing the socioeconomic profiles of people with disabilities, particularly their access to health, education, and social protection services. Chapter three includes an analysis of current public policies and of the legal and institutional framework for the protection and promotion of the rights of people with disabilities in Sierra Leone. Chapter four provides an overview of the current public and private programs to support people with disabilities, with a focus on their objectives, costs, limitations, and impact. Most of these programs have been in direct response to the conflict and have had an emergency nature, at times disregarding some of the more structural issues concerning people with disabilities and the needs of those people whose disability is only indirectly related to the conflict. The final chapter, chapter five, outlines possible options to reform the overall public/private approach to people with disabilities, and explores options for inclusive policies and programs to support people with disabilities including sector interventions to improve their standard of living.